Flavonoids and the regulation of seed size in Arabidopsis. (20th March 2014) - Doughty, James; Aljabri, Maha; Scott, Rod J.
Abstract : Understanding how seed size is regulated in angiosperms is a key goal for plant science as seed size is an important component of overall seed yield. Angiosperm seeds comprise three clearly defined components, i.e. the embryo, endosperm and seed coat, with each having a distinct genetic composition which exerts different influences on seed development. Complex cross-talk and integration of signals from these different regions of the seed together determine its final size. The present review considers some of the major regulators of seed size, with a particular emphasis on the role of the seed coat in modulating endosperm proliferation and cellularization. The innermost layer of the seed coat, the endothelium, synthesizes flavonoids which are held to provide a defensive function against microbes, act as feeding deterrents, provide UV protection and to have a role in seed dormancy. A growing body of data suggests that flavonoids may also play a fundamental role in regulating communication between the seed coat and the endosperm. In the present review, we discuss how this may be achieved in the light of the fact that several flavonoids are known to be potent auxin transport regulators.